Matilha cultural: espaço de novas configurações e de formação política dos sujeitos coletivos na cidade de São Paulo - Couto, Mariana Melo Gomes do (2020)
This dissertation has as its research subject, the Matilha Cultural, a space of cultural dissemination located in the central area of São Paulo that has at its core concepts related to coexistence, freedom and the common good. Opening space for the dissemination of street art and art in the periphery The goals of this dissertation is to decipher the Matilha Cultural and understand how the new configurations of cultural spaces and the political formation of collective subjects take place from the cultural perspective of resistance and insurgency.. Matilha Cultural is considered the meeting point of the peripheries, particularly because of the themes addressed in its activities, the openness for free or voluntary collaboration, and the easy access by public transit.. The specific goals of this dissertation is to examine who the attendees of Matilha Cultural are; to investigate whether the activities developed at Matilha Cultural encourage critical consciousness and the common good; and to verify whether its agenda constitutes an act of insurgency according to the dynamics of culture in the periphery. The theoretical framework for this research includes a qualitative methodology. Documentary research was also conducted through electronic media, newspaper and magazine articles, and websites that cited Matilha Cultural. Empirical research was conducted through semi-structured interviews with the people who participate in the activities offered there as well as the person in charge of Matilha Cultural. Direct observation of the center’s various activities was also used to structure this research. The findings of this dissertation reinforce the importance of building alternative spaces of cultural formation that are committed to a critical reading of society as well as the democratization of knowleges that strengthen social movements and, above all, provide a different outlook for the production of culture in the periphery, recognizing its legitimacy and its potential for transformation